The Effectiveness of an Educational Program Using the Pentagram Strategy in Improving the ‎Achievement and Teaching Competencies of Fine Arts Students - Mohammed, Jawad Kadhum (Dirasat: Human and Social Sciences, 2025)
Objectives: The study aims to explore the effectiveness of an educational program using the Pentagram strategy in improving academic achievement in the "Observation and Application" course, as well as enhancing teaching competencies among Fine Arts students. Methods: The researcher employed an experimental design with two groups: a control group and an experimental group. The educational program was structured according to the steps of the "Pentagram" strategy, which included defining general objectives, organizing the educational content, formulating behavioral objectives, conducting a pre-test, incorporating learning activities and resources, utilizing educational technologies, and implementing both formative and final assessments. A purposive sample of 60 fourth-year students from the Department of Art Education at the College of Fine Arts, University of Wasit, was selected for the study. To measure outcomes, the researcher developed an achievement test for academic performance and a scale to assess teaching competencies. Results: The results showed the effectiveness of the educational program, as students in the experimental group, who were taught using the "Pentagram" strategy, outperformed students in the control group, who were taught using traditional methods, in both the achievement test and teaching competencies. Conclusions: The researcher concluded that the use of the "Pentagram" strategy had a positive effect, contributing to an increase in the academic achievement of fourth-year students in the "Observation and Application" course. The educational program also proved to be effective in improving the teaching competencies of the student teachers.